2003
DOI: 10.1021/cm0340734
|View full text |Cite
|
Sign up to set email alerts
|

General Method for Chiral Imprinting of Sol−Gel Thin Films Exhibiting Enantioselectivity

Abstract: Chirally imprinted sol-gel thin films were fabricated through the molecular imprinting technique. The films were spin coated on glass plate substrates. Enantioselective discrimination of these films was observed toward three different templates. In each case a different enantiomer pair was selected as a template and a sol mixture was tailored accordingly. By extracting the template molecule a defined chiral cavity was created. The enantiomer pairs were (R)-and (S)-propranolol, (R)-and (S)-2,2,2-trifluoro-1-(9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 54 publications
3
57
1
Order By: Relevance
“…A very illustrative example can be given by the entrapment of chiral molecules. Depending on how a chiral template is applied to the sol-gel process it can lead to the formation of quiral pores [74] that after the template removal will be selective for that enantiomer used [75], or even the whole gel structure can self-assemble to a helical structure obeying the template's chirality (Figure 3c) [76]. In the sol-gel process, ILs not only act as templates, but have ability to stabilize the structures formed, working as efficient templates/solvents [67] and, in some cases templates/solvents/reactants [77].…”
Section: Introductionmentioning
confidence: 99%
“…A very illustrative example can be given by the entrapment of chiral molecules. Depending on how a chiral template is applied to the sol-gel process it can lead to the formation of quiral pores [74] that after the template removal will be selective for that enantiomer used [75], or even the whole gel structure can self-assemble to a helical structure obeying the template's chirality (Figure 3c) [76]. In the sol-gel process, ILs not only act as templates, but have ability to stabilize the structures formed, working as efficient templates/solvents [67] and, in some cases templates/solvents/reactants [77].…”
Section: Introductionmentioning
confidence: 99%
“…110 Chiral imprinting of sol-gel thin films exhibiting enantioselectivity has been developed by David Avnir's group. In a series of articles, Avnir et al [111][112] showed that template molecules such as propranolol, 2,2,2-trifluoro-1-(9-anthryl) ethanol, DOPA, and tyrosine can be used to prepare a chiral imprint sol-gel matrix. The shape of the chiral matrix is maintained when the template molecule is extracted.…”
Section: Template-based Imprinting Approachmentioning
confidence: 99%
“…These techniques fall into at least two categories: vacuum-based methods such as chemical vapor deposition (CVD), 19 sputtering, 20 metal organic chemical vapor deposition (MOCVD), 21 atomic layer deposition (ALD), 22 and chemical solution methods including sol-gel, electrochemical deposition, and hydrothermal synthesis. 23,24 Vacuum-based techniques are an expensive investment, are limited to line-of-sight production, and usually require highvapor-pressure chemicals or high-purity targets as starting materials. For conventional CVD methods, precursors exhibiting volatility are needed, which requires that the precursor is liquid or solid with a low melting point.…”
Section: 2mentioning
confidence: 99%